Subsets of follicular lymphoma 3B have divergent outcomes: results from the prospective multicenter MER and LEO cohorts - Patrizia Mondello; Brianna Negaard; Andrew L. Feldman; Brian K. Link; Carla Casulo; Dai Chihara; David Russler-Germain; Jason Romancik; Caitlin Gribbin; Sara Haddadi; Eric Mou; Ivana N. Micallef; et al. (Blood Cancer Journal)
Abstract Follicular lymphoma (FL) 3B is considered an aggressive lymphoma, however recent studies have challenged this paradigm. Additional controversy involves the clinical implication of pure FL3B (FL3Bp) vs FL3B with concurrent diffuse large B cell lymphoma (DLBCL) (FL3Bc). To address these questions, we performed a pooled study of the MER and LEO cohorts comparing 464 newly diagnosed, R-CHOP-treated patients with FL1-2 (n = 216), FL3A (n = 170), FL3B (n = 78) and 739 DLBCL. Among FL3B patients, 19 (24%) had FL3Bc and 59 (76%) FL3Bp. Baseline characteristics and outcomes were similar between the two FL3B subtypes. Compared to FL1-3A, FL3B showed similar clinical features, except for a lower tumor burden. After R-CHOP, FL1-2 patients had an inferior event-free survival (EFS) than those with FL3B, whereas there was no difference with FL3A. Survival was similar across the FL grades. Although FL1-2 patients failed to achieve EFS24 more frequently than FL3B and FL3A, FL3B patients who failed EFS24 had three-fold higher risk of subsequent mortality than other FLs. At 5-year follow-up FL3B patients had twice the risk of relapse with an aggressive subtype than those with FL1-2 and FL3A. Compared to DLBCL, FL3B patients had more favorable clinical features, but similar outcomes to GCB subtype. Our data suggest that most FL3B have a good outcome, while a subset has an aggressive behavior.